One-Step Ultrafiltration Process for Separation and Purification of a Keratinolytic Protease Produced with Feather Meal. (28th June 2018) - Machado, Juliana R.; Severo, Emanuelle E.; de Oliveira, Janaina M. G.; Ores, Joana da C.; Brandelli, Adriano; Kalil, Susana J.
Abstract : A purification technique to obtain keratinolytic proteases produced by Bacillus sp. P45 in a medium containing chicken feather meal as substrate is presented. The experiments were carried out in a dead-end ultrafiltration unit, and the influence of the membrane cutoff, pH of enzymatic extract, and operating pressure on the purification of keratinase were studied. The one-step ultrafiltration process with the membrane molecular mass cutoff of 10 kDa at pH 8.0 and operating pressure of 0.147 MPa showed an enzyme recovery of 87.8% and a 4.1-fold purification factor. It is showed that ultrafiltration could be potentially used in the purification of keratinases.